Diffusion of Ions in Phosphonium Orthoborate Ionic Liquids Studied by 1H and 11B Pulsed Field Gradient NMR - Filippov, Andrei; Munavirov, Bulat; Glavatskih, Sergei; Shah, Faiz Ullah; Antzutkin, Oleg N. (Frontiers in Chemistry, 2020)
Non-halogenated boron based ionic liquids (ILs) composed of phosphonium cations and chelated orthoborate anions have a high hydrolytic stability, a low melting point and exceptional properties in various applications. This study is focussed on ILs with the same type of cation – trihexyltetradecylphosphonium ([P6,6,6,14]+) and two orthoborate anions, such as bis(salicylato)borate ([BScB]-) and bis(oxalato)borate ([BOB]-), and compared with our previous studies on ILs with bis(mandelato)borate ([BMB]-) and a variety of different cations (tetraalkylphosphonium, dialkylpyrrolidinium and dialkylimidazolium). The ion dynamics and phase behavior of these ILs is studied using 1H and 11B pulsed-field-gradient (PFG) NMR technique. PFG NMR is demonstrated to be a useful tool to elucidate the dynamics of ions in this class of phosphonium orthoborate ionic liquids. In particular, applicability of 11B PFG NMR for anions without 1H, such as in [BOB]- and the limitations of this technique to measure self-diffusion of ions in ILs are demonstrated and discussed in detail for the first time.